Crystal structure and Hirshfeld surface analysis of a conformationally unsymmetrical bischalcone: (1E,4E)-1,5-bis(4-bromophenyl)penta-1,4-dien-3- one - Tawfeeq, Nabeel Arif; Kwong, Huey Chong; Mohamed Tahir, Mohamed Ibrahim; Ravoof, Thahira B. S. A. (International Union of Crystallography, 2019)
In the title bischalcone, C17H12Br2O, the olefinic double bonds are almost coplanar with their attached 4-bromophenyl rings [torsion angles = −10.2 (4) and −6.2 (4)°], while the carbonyl double bond is in an s-trans conformation with with respect to one of the C=C bonds and an s-cis conformation with respect to the other [C=C—C=O = 160.7 (3) and −15.2 (4)°, respectively]. The dihedral angle between the 4-bromophenyl rings is 51.56 (2)°. In the crystal, molecules are linked into a zigzag chain propagating along [001] by weak C—H⋯π interactions. The conformations of related bischalcones are surveyed and a Hirshfeld surface analysis is used to investigate and quantify the intermolecular contacts.